2018
DOI: 10.1021/acs.chemmater.8b01149
|View full text |Cite
|
Sign up to set email alerts
|

Cascade-Promoted Photo-Chemotherapy against Resistant Cancers by Enzyme-Responsive Polyprodrug Nanoplatforms

Abstract: Cisplatin has long been the first-line treatment for a variety of solid tumors. However, the poor pharmacokinetics and intrinsic or acquired drug resistance are the main challenges in cancer therapy. Herein, endogenous enzymeresponsive cisplatin polyprodrug nanoplatforms were developed for cascade-promoted photo-chemotherapy against drugresistant cancers. The polyprodrug nanoplatforms, ICG/Poly(Pt), were fabricated from the indocyanine green (ICG) photosensitizer and cisplatin polyprodrug amphiphiles, PEG-b-P(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 81 publications
(115 reference statements)
2
66
0
Order By: Relevance
“…At 12 hp ost-injection, the PA signal was much weaker than that of 3h post-injection, indicating the almost complete clearance of the TFM NPs. [34] After intravenous injection with TFM NPs sized % 72 nm for 4h,t he tumor fluorescence was much more significant than that of TFM NPs sized % 180 nm (Figure S20 a). [32,33] These results solidly demonstrated that TFM NPs possess ap rominent EPR effect, enabling them to efficiently accu-mulate in tumor tissue combined with rapid clearance,t hus making them excellent agents for PA Ii nahigh-contrast and safe manner.…”
Section: As Shown Inmentioning
confidence: 97%
See 1 more Smart Citation
“…At 12 hp ost-injection, the PA signal was much weaker than that of 3h post-injection, indicating the almost complete clearance of the TFM NPs. [34] After intravenous injection with TFM NPs sized % 72 nm for 4h,t he tumor fluorescence was much more significant than that of TFM NPs sized % 180 nm (Figure S20 a). [32,33] These results solidly demonstrated that TFM NPs possess ap rominent EPR effect, enabling them to efficiently accu-mulate in tumor tissue combined with rapid clearance,t hus making them excellent agents for PA Ii nahigh-contrast and safe manner.…”
Section: As Shown Inmentioning
confidence: 97%
“…Thei nvivo biodistribution of the TFM NPs was examined by encapsulating slightly fluorescent indocyanine green (ICG). [34] After intravenous injection with TFM NPs sized % 72 nm for 4h,t he tumor fluorescence was much more significant than that of TFM NPs sized % 180 nm (Figure S20 a). Them ore efficient tumor accumulation of TFM NPs with as ize of % 72 nm was also confirmed by ex vivo fluorescence imaging of isolated tissues (Figure S20 b,c), indicating that the tumor accumulation potency of the TFM NPs with as maller size was superior,w hich was optimized for efficient theranostics.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Upon cellular uptake in lysosomes, ICG could induce local hyperthermia and ROS under NIR light irradiation and it could also assist the escape of cisplatin prodrugs into the reductive cytosol by damaging lysosomes. 34 In addition, the combination treatment of PDT can benefit from pathogen inhibition. Liu et al developed azonia-containing polyelectrolytes with extraordinary performance for ROS generation for antibacterial applications.…”
Section: Combination Therapy Of Ptt and Itmentioning
confidence: 99%
“…Furthermore, it was observed that the size of the TFM NPs can be increased to ≈180 nm by enhancing the feed content of TFM and PEG‐ b ‐PLA in the formation of the TFM NPs (Figure S19). The in vivo biodistribution of the TFM NPs was examined by encapsulating slightly fluorescent indocyanine green (ICG) . After intravenous injection with TFM NPs sized ≈72 nm for 4 h, the tumor fluorescence was much more significant than that of TFM NPs sized ≈180 nm (Figure S20 a).…”
Section: Figurementioning
confidence: 99%